COMPARISON SPIRAL PIPE WITH ROUND PIPE FOR HEAT TRANSFER IN BOILER GAS TURBINE - Ismail Thamrin; K Novaldo (Indonesian Journal of Engineering and Science (IJES), 2020)
The increasing need for energy requires finding alternative energy. Sawdust is wate but can be utilised as alternative energy. The sawdust is used as a boiler fuel called biomass. However, the utilization of sawdust as a boiler fuel is considered less effective. Presumably heat and mass transfer of steam for boiler system using spiral pipes. Since the length of steam distribution becomes long so that the heat transfer from boiler to pipes takes a long time. Thus, this study examines the effect of spiral pipes for the heat transfer process for boilers, where the steam is supplied to rotate the turbines (generate electricity). Based on initially study, the boiler system performance using spiral pipe is better than round pipe.